Chinese labour in South Africa, 1902-10 : race, violence, and global spectacle - Bright, Rachel, 1979- (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
"At the beginning of the twentieth century, 'white' colonies around the world had restricted Asian migration, associated with immorality, disease, and a threat to 'white' labour. The 'Yellow Peril' was in full swing. And yet, in 1904, the British government imported over 64,000 Chinese indentured labourers to work on gold mines in Southern Africa. This book explores the decision to import Chinese labour so soon after the empire had fought to secure Southern Africa for the British Empire and despite the already tense racial situation in the region. This enables a clearer understanding of racial and political developments in Southern Africa during the reconstruction period and the formation of South Africa the nation. It places these localised issues within a wider historiography, such as research into colonial violence, moral panics and Black Perils, networks of labourism and whiteness, and economic imperialism. Through this book one can trace the complicated negotiations between national and imperial identities, between independence and patriotism, and giving a clearer sense of how trans-colonial relationships evolved"--
1. Chinese Migration and "White" Networks, c.1850-1902 -- 2. The Transvaal Labour 'Problem" and the Chinese Solution -- 3. Greater Britain in South Africa : Colonial Nationalisms and Imperial Networks -- 4. A Question of Honour : slavery, sovereignty and the legal framework -- 5. Sex, Violence and the Chinese : The 1905-6 Moral Panic -- 6. Adapting the Stereotype : Race and Administrative Control -- 7. Political Repercussions -- Conclusion: Racializing Empire -- Appendix A: List of Key Figures.
Includes bibliographical references (pages 197-261) and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Chinese -- South Africa -- History -- 20th century; Contract labor -- South Africa -- History -- 20th century; Immigrants -- South Africa -- History -- 20th century; Violence -- South Africa -- History -- 20th century; Imperialism -- History -- 20th century; Imperialism -- Economic aspects -- History -- 20th century; South Africa -- Race relations -- History -- 20th century; South Africa -- Emigration and immigration -- History -- 20th century; South Africa -- Politics and government -- 1836-1909.; Great Britain -- Colonies -- Africa -- History -- 20th century; Electronic books